AGREEMENT on Cooperation on Marine Oil Pollution Preparedness and Response in the Arctic. - Arctic Council (Arctic Council Secretariat, 2013)
"AGREEMENT on Cooperation on Marine Oil Pollution Preparedness and Response in the Arctic The Government of Canada, the Government of the Kingdom of Denmark, the Government of the Republic of Finland, the Government of Iceland, the Government of the Kingdom of Norway, the Government of the Russian Federation, the Government of the Kingdom of Sweden, and the Government of the United States of America, hereinafter referred to as “the Parties” /./"